Interaction of sol–gel derived TiO2 ‐ and SiO2 ‐based bionanocomposites with erythrocytes and serum proteins. Issue 1 (1st March 2013) - Banu, A. Shakila; Devi, S. Vimala; Prakash, T.
Abstract : Nanoenabled drug carriers are emerging as alternatives to conventional small‐molecule drugs and their in‐vitro biocompatibility evaluation with blood components is a necessary part of early preclinical development. In the present study, Chitosan‐based bionanocomposites of sol–gel derived TiO2 and SiO2 were synthesised by the ex situ process. Samples were characterised by X‐ray diffraction, Fourier transformed infrared spectrophotometer, transmission electron microscopy and selected area electron diffraction techniques. The analysis reveals the formation of single‐phase oxides and their bionanocomposites. Haemolysis (destruction of red blood cell) study was performed by spectrophotometer to assess the haemocompatibility nature as a function of different incubation time. Experimental results reveal the percentage of haemolysis increase with the increase of the incubation time, but it was found to be <2%. This confirms our bionanocomposites are more haemocompatible as compared with respective nanocrystalline ceramics. Also, the interaction of our bionanocomposites with serum proteins at various incubation periods (1–24 h) were investigated using sodium dodecyl sulphate–polyacrylamide gel experiment, the obtained results were discussed in details.